PERILAKU MAHASISWA TERHADAP PENGGUNAAN e-SIM AKADEMIK SEBAGAI SARANA PENUNJANG PELAYANAN AKADEMIK - Setiawan, Budi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
This research aims at identifying student behaviors toward the use of electronic academic information system at STIA LAN Bandung. This research employs a model once applied by Asmoro and Gardner (2004) in their research to internet users. The model is called Technology Acceptance Model (Davis, 1989) which is widely used in information system research. The model was then developed by incorporating external variables comprising gender, complexity, experience, and voluntariness.In this research, the data were collected through questionnaires distributed to students of STIA LAN Bandung who had already utilized e-SIMAK. 116 respondents returned the questionnaires and, by using Partial Least Square, 95 of them wereworthy of being analyzed. The result shows that the obligation to use e-SIMAK causes less significant influence of behavioral intention to actual use. In addition, complexity significantly influences actual use. Meanwhile, gender also contributes significant influence to perceived ease of use.